2017
DOI: 10.1002/jor.23587
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin inhibits inflammation‐induced osteoclastogenesis and bone resorption

Abstract: Osteoclasts play key roles in bone remodeling and pathologic osteolytic disorders such as inflammation, infection, bone implant loosening, rheumatoid arthritis, metastatic bone cancers, and pathological fractures. Osteoclasts are formed by the fusion of monocytes in response to receptor activators of NF-κB-ligand (RANKL) and macrophage colony stimulating factor 1 (M-CSF). Calreticulin (CRT), a commonly known intracellular protein as a calcium-binding chaperone, has an unexpectedly robust anti-osteoclastogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…However, contradictory to the proinflammatory role of CALR, recent reports also showed that CALR may have an anti-inflammatory function in other animal models. For example, Fischer et al recently reported that recombinant human CALR can inhibit lipopolysaccharide (LPS)induced inflammatory osteoclastogenesis in the mouse calvarial bone (35). Another report indicated that intraperitoneal injection of recombinant CALR fragment 39-272 (CRT/39-272) into animal model with experimental autoimmune encephalomyelitis (EAE) can significantly reduce the disease severity of EAE (36).…”
Section: Introductionmentioning
confidence: 99%
“…However, contradictory to the proinflammatory role of CALR, recent reports also showed that CALR may have an anti-inflammatory function in other animal models. For example, Fischer et al recently reported that recombinant human CALR can inhibit lipopolysaccharide (LPS)induced inflammatory osteoclastogenesis in the mouse calvarial bone (35). Another report indicated that intraperitoneal injection of recombinant CALR fragment 39-272 (CRT/39-272) into animal model with experimental autoimmune encephalomyelitis (EAE) can significantly reduce the disease severity of EAE (36).…”
Section: Introductionmentioning
confidence: 99%
“…CRT is also an endoplasmic reticulum chaperone and is involved in endoplasmic reticulum stress to prevent protein unfolding, but is downregulated in cholesteatoma. Fischer et al (35) reported that CRT inhibited lipopolysaccharideinduced inflammatory osteoclastogenesis and bone resorption. With the lytic enzymes and cytokines produced in cholesteatoma, the inflammatory condition may further promote epithelial proliferation in cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because in aged people the calcium homeostasis is usually altered, changes in calcium signaling and/or binding proteins have been proven to be effective markers of cellular and tissue dysfunction in these patients. The three "calcium homeostasis" biomarkers of fragility are S100B (S 100 calcium binding protein B) [84]; SMP30 (senescence-marker protein 30) [85]; calreticulin (a multifunctional protein initially identified as a Ca 2+ storage protein) [86]. Both regucalcin and calreticum reached high priority.…”
Section: Crosstalk Between Frailty and Cardiovascular Diseases In Molmentioning
confidence: 99%